2016
DOI: 10.1038/ja.2016.39
|View full text |Cite
|
Sign up to set email alerts
|

General base-general acid catalysis by terpenoid cyclases

Abstract: Terpenoid cyclases catalyze the most complex reactions in biology, in that more than half of the substrate carbon atoms often undergo changes in bonding during the course of a multistep cyclization cascade that proceeds through multiple carbocation intermediates. Many cyclization mechanisms require stereospecific deprotonation and reprotonation steps, and most cyclization cascades are terminated by deprotonation to yield an olefin product. The first bacterial terpenoid cyclase to yield a crystal structure was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 65 publications
2
27
0
Order By: Relevance
“…The water bound in the cavity created by substitution of Ala for this Ile would then similarly enable the effects on product outcome observed here with such I→A mutants of KSs ( Figures 3 and 4 ). In this mechanism the general base is most likely the pyrophosphate anion co-product, as previously suggested for class I terpene synthases in general (Pemberton and Christianson, 2016). …”
Section: Discussionmentioning
confidence: 52%
“…The water bound in the cavity created by substitution of Ala for this Ile would then similarly enable the effects on product outcome observed here with such I→A mutants of KSs ( Figures 3 and 4 ). In this mechanism the general base is most likely the pyrophosphate anion co-product, as previously suggested for class I terpene synthases in general (Pemberton and Christianson, 2016). …”
Section: Discussionmentioning
confidence: 52%
“… 271 Additionally, the negative electrostatic potential of the inorganic pyrophosphate coproduct provides electrostatic stabilization of carbocation intermediates. Inorganic pyrophosphate may also serve widely as a general base to terminate the reaction sequence in class I terpenoid cyclization and coupling reactions, 3 , 75 , 80 and a water molecule may serve this function in class II terpenoid cyclases. 429 For class I or class II cyclases in which a water molecule adds to the final carbocation intermediate to terminate the reaction, the water molecule must be highly controlled so that it does not prematurely quench the sequence of carbocation intermediates in the cyclization cascade.…”
Section: Discussionmentioning
confidence: 99%
“…Since this water molecule is located near the geminal dimethyl group of 2-azabornane and (+)-bornyl diphosphate, which accordingly would be in the vicinity of the geminal dimethyl group of the α-terpinyl cation intermediate, it is possible that this water molecule hydroxylates the α-terpinyl cation in the cineole synthase mechanism. Given the likely role of coproduct inorganic pyrophosphate as a potential general base-general acid catalyst, 80 inorganic pyrophosphate may deprotonate this water molecule upon hydroxylation of the α-terpinyl cation and then protonate the carbon–carbon double bond of α-terpineol to enable cineole formation as shown in Figure 41 .…”
Section: Class I Terpenoid Cyclasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the perceived lack of side chains with suitable basicity has led to the hypothesis that the pyrophosphate anion co-product ( -OPP) generally serves as the catalytic (general) base. 2 Previous work has demonstrated that single residue changes can switch product outcome in certain plant diterpene synthases. [3][4][5][6][7][8][9][10][11] Arguably the most interesting changes are those involving a key position that controls the complexity of the catalytic reaction.…”
mentioning
confidence: 99%